Taphonomic studies with wild brown bears (Ursus arctos) in the mountains of northern Spain - Sala Burgos, Nohemi; Arsuaga Ferreras, Juan Luis (Journal of Archaeological Science, 2013)
In this work we present data obtained from experiments with wild brown bears from the Cantabrian Mountains in northern Spain. Our results show that wild brown bears do not take carcasses to their dens, but can displace them by tens of meters before eating them, and the remains can become dispersed some meters around the place where the carcass is consumed. The long bones of large-sized carcasses show no fractures, but they do show tooth marks (scores, pitting, punctures and furrowing) especially on the cancellous bone of the epiphyses. Ribs and vertebrae show fractures and furrowing. The innominate also shows furrowing on cancellous bone of the ilium and ischium. The results of this study are in agreement with previous work and also shed some light on the behavior of this carnivore in the wild. The data gathered are of great importance when interpreting paleontological and archaeological sites where the bear is a likely taphonomic agent. Ministerio de Educación Ministerio de Ciencia e Innovación (MICINN) Depto. de Geodinámica, Estratigrafía y Paleontología Fac. de Ciencias Geológicas TRUE pub